Risk Factors of Malaria Incidence in the Work Area of Wakadia Health Center Muna Regency - Adryana, Vita; Sunarsih, Sunarsih; Nirwan, M. (Waluya The International Science of Health Journal, 2023)
Backgrounds: Malaria has long been one of the highest causes of death in the world, including in Indonesia. For the last three years, Muna Regency has been the area with the highest malaria cases in Southeast Sulawesi, where in 2020 there were 102 cases, in 2021 there were 97 cases, and in 2022 there were 80 cases. This study aims to analyze the risk factors for malaria incidence in the Work Area of ​​the Wakadia Public Health Center, Muna Regency. Methods: This research is a quantitative study using the Case Control Study method. The study population was all patients with microscopic examination results (positive for malaria) in 35 cases. The research sample consisted of a case sample and a control sample totaling 70 people. Data collection was carried out by observation and interviews using a questionnaire. Analysis of the research data was carried out descriptively and inferentially using the Odd Ratio test. Results: The results showed that air temperature (OR= 3.545) dan habit of using mosquito-repellent drugs (OR= 3,273), Conclusion: Air temperature and the habit of using mosquito-repellent drugs are risk factors for the incidence of malaria in the Work Area of ​​the Wakadia Public Health Center, Muna Regency.